Evaluation Indonesian Financial Performance of Islamic Commercial Bank using Gaussian Mixture Model with Intervention Analysis - Syalsabilla, Alya Fitri; Astutik, Suci; Shahuneeza Naseer, Mariyam (Universitas Islam Negeri Raden Intan Lampung, 2024)
Indonesia, with its rich diversity and sizable Muslim population, holds a prominent position in global Islamic finance. Financial ratios like ROA, CAR, NPF, FDR, BOPO, and NOM are crucial for assessing bank performance. Employing Gaussian Mixture Model with Intervention Analysis enhances evaluation by identifying outliers and understanding their impact.Utilizing Islamic Banking Statistics from January to December 2023, this research employs purposive sampling to select relevant variables like CAR, NPF, FDR, BOPO, NOM, and ROA. Gaussian Mixture Model identifies data patterns, while Intervention Analysis examines factors affecting Islamic banking performance.Financial performance analysis reveals shifts from